Pengaruh Likuiditas, Profitabilitas, dan Ukuran Perusahaan terhadap Nilai Perusahaan: Studi Empiris dari Perusahaan Barang Konsumen Primer yang Tercatat di BEI Tahun 2020-2023 - Siti Alisia Asri Suprapto; Muslimin Muslimin (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study analyzes the effect of liquidity, profitability, and firm size on firm value in consumer non-cyclicals manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. The research aims to identify internal financial factors influencing firm value in essential goods industries. Secondary data from financial reports and the official IDX website was analyzed using a quantitative methodology. Purposive sampling was used to choose 25 of the 130 enterprises that made up the population.  Price to book value, current ratio, return on assets, and firm size were used to determine the firm's value.  Panel data regression was utilized to evaluate the data.  According to the findings, firm size has no discernible impact on firm value, profitability has a considerable positive impact, and liquidity has a big negative impact.  According to these results, a firm's worth is significantly shaped by its financial performance, particularly by its ability to manage liquidity and generate profits.  This study is unique since it focuses on the consumer non-cyclicals sector and uses current post-pandemic panel data. In conclusion, rofitability is a key driver of firm value, while excessive liquidity may reduce investor confidence.